2014 Eleventh Annual IEEE International Conference on Sensing, Communication, and Networking (SECON) 2014
DOI: 10.1109/sahcn.2014.6990334
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering a Hidden wireless menace: Interference from 802.11x MAC acknowledgment frames

Abstract: Abstract-Previous work on 802.11x (Wi-Fi) power control have focused almost exclusively on the mitigation of interference from data frames. Since Wi-Fi wireless access points are increasingly ubiquitous, it is now common for an 802.11x client to be able to receive signals from more than 10 APs simultaneously in a modern urban operating environment. At such high densities, we found that the interference from the MAC acknowledgment (ACK) frames can potentially reduce throughput by several fold. We show that by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…We can also see two distinct bandings with about 25% of the frames having an air time of 20 µs and 20% at 190 µs. Upon closer inspection, we found that the former 20 µs frames were MAC ACK frames [21] and the latter frames were multicast frames arising from the Neighbor Discovery Protocol of IPv6.…”
Section: Interfering Frame Air Time Mattersmentioning
confidence: 99%
See 2 more Smart Citations
“…We can also see two distinct bandings with about 25% of the frames having an air time of 20 µs and 20% at 190 µs. Upon closer inspection, we found that the former 20 µs frames were MAC ACK frames [21] and the latter frames were multicast frames arising from the Neighbor Discovery Protocol of IPv6.…”
Section: Interfering Frame Air Time Mattersmentioning
confidence: 99%
“…To generate interference from AP-2, we connected another client (not shown in Figure 2) to AP-2 and sent a 1,500-byte non-saturating UDP flow to this interfering client from another machine in our laboratory. To mitigate MAC ACK interferences [21] from the interfering client, the interfering client was positioned further away from AP-1's client (i.e., on the "other" side of AP-2) and also operated at reduced transmission power. For each test, the UDP flows ran for 30 s and we measured the throughput obtained by AP-1's client.…”
Section: Impact Of Mim: a Qualitative Studymentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, without using circuits such as LNA or BPF, it is possible to detect hidden cameras, which emits low signals and works as WLAN, only by phone and software as detecting hidden wireless camera (DeWiCam) [12]. Wang W. et al were succeeded at uncovering hidden wireless threat by the help of interference method [13].…”
Section: Introductionmentioning
confidence: 99%
“…In [12], the loss of ACK due to the hidden node problem is studied in multihop wireless networks. In [13], the loss of data frames by the interference from ACK transmission in adjacent cells due to the hidden node problem is studied.…”
Section: Introductionmentioning
confidence: 99%